COVID-19 and its effects on social connectedness among Malaysian Malay living abroad - Nur Farah Wani Mohd Nasir; Julia Abyana Aziya; Nur Hafeeza Ahmad Pazil (Penerbit Universiti Kebangsaan Malaysia, 2022)
Ever since the global pandemic COVID-19 emerged, governments all around the world have attempted to slow the spread of this disease by promoting social isolation and social distancing. Although physical separation does curtail the spread of the virus, the practice of social distancing has limited people’s in-person social interactions and has narrowed their sense of social connectedness. To Malaysian Malay expatriates, social connectedness is more than just a means of social relationship or social networking. Social connectedness is a motivating factor for survival and a way to reduce feelings of social anxiety and frustrations when living in a foreign host country. To highlight the significance of social connectedness while working abroad, this study was conducted with 11 single Malaysian Malays residing in the United States of America, United Kingdom, Australia, and Canada. A qualitative approach was employed in this study by using in-depth interviews to examine the socio-cultural challenges they experienced while working and living in a country different from their own. This paper discusses how COVID-19 affects Malaysian Malay expatriates’ social connectedness while living abroad in host countries and the need for more research exploration in the subject area. As a result, although social media can be a platform for everyone to be connected, face-to-face interactions are more desirable. Furthermore, the researchers also found that practising a level of intimacy with close friends can help Malaysian Malay expatriates to gain social connectedness with others which also leads to the feeling of belongingness in their community.